Generalized moment representations, biorthogonal polynomials, and Padé approximants - Holub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using the method of generalized moment representations and certain properties of biorthogonal polynomials, we establish new invariance properties of the Padé approximants.